The Role of Wakalah Contract Implementation in Increasing Interest in Becoming A Reseller - Mohammad Fatchur Roziq; Sundari; Muhammad Mujtaba Mitra Zuana (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
Online stores provide offers and convenience in doing business in the current era, starting from offering initial capital, and shipping goods to storage/warehouses. The rapid development of information technology has had an impact on the large growth of online stores, one of which is fashion resellers from children, teenagers to adults. Fayana is an online store that implements a reseller recruitment program to market its products using the Wakalah Agreement, As-Salam Contract, Wa’ad Contract, and Istishna. This study aims to analyze the role of implementing wakalah contracts in increasing interest in becoming a reseller at the Fayana Collection Store Surabaya. The research uses a qualitative approach. The results of this study showed that the implementation of the Wakalah Agreement played a role in increasing the interest of resellers to join Fayana Stores, in addition to one of the advantages of this store there was also an increase in the discount rate from 5% to 20%.